Fame-bridging, stereotypes, and the celebrity labour of Anna Nicole Smith. Issue 4 (2nd October 2021) - Donovan, Brian; Neumann, Elyse
ABSTRACT: When actor and model Anna Nicole Smith died in 2007 she was known to the public through two central stereotypes: gold digger and white trash. Likewise, the news and entertainment media remembered Smith as 'famous for being famous', not for her ostensible talent or entrepreneurship. We critique the dominant understandings of Smith through a critical reading of cultural production by and about her. Analysis of Smith's celebrity and its cultural antecedents allows for a better understanding of the production of celebrity and a greater appreciation of what it means to be 'famous for being famous'. A careful consideration of Smith's controversial life and work reveals an instance of celebrity where gender, race, and class-based stereotypes worked to delegitimize her celebrity labour. Specifically, interlocking stereotypes undermined Smith's attempt at 'fame-bridging', cultural work she did to forge a link between Marilyn Monroe and her own claim to fame.